Improving gain of ultra-wideband planar antennas: a grounded frequency-selective surface reflector - Ahmed Jamal Abdullah Al-Gburi; Zahriladha Zakaria; Khaled Alhassoon; Imran Mohd Ibrahim; Jamil Abedalrahim Jamil Alsayaydeh (Universitas Ahmad Dahlan, 2023)
This paper introduces a method to enhance the gain of ultra-wideband (UWB) planar antennas by employing a grounded frequency-selective surface (FSS) as a reflector. The grounded FSS reflector comprises square patch structures (SPSs) of unit cells with a complete ground plane. The designed FSS utilizes miniaturized unit cells that are printed on both sides of an FR4 substrate, making it highly suitable for a wide range of applications, particularly as a reflector to optimize the gain of UWB omnidirectional radiators. This concept is demonstrated by employing a circular monopole UWB antenna as the radiator. The measured outcomes of the suggested antenna with the grounded FSS maintain a broad frequency range of bandwidth of 9.162 GHz, spanning from 2.638 GHz to 11.8 GHz. The antenna, in combination with the FSS, achieves a significant measured gain of 7.6 dBi and a high efficiency of 93% at 9.6 GHz. The attributes of the suggested UWB FSS make it an ideal solution for seamless combining with small-sized broadband circuits, thereby maximizing its effectiveness.